Why geriatric medicine? A survey of UK specialist trainees in geriatric medicine - Fisher, James M.; Garside, Mark J.; Brock, Peter; Gibson, Vicky; Hunt, Kelly K.; Briggs, Sally; Gordon, Adam L. (Oxford University Press, 2017)
Background: There is global concern that there are insufficient numbers of geriatricians to meet the needs of the ageing population. A 2005 survey described factors that influenced why UK geriatricians had chosen to specialise in the field - in the decade since, UK postgraduate training has undergone a fundamental restructure.